Evidence of nitrite acting as a stable and robust inducer of non-cultivability in Mycobacterium tuberculosis with physiological relevance - Gample, Suwarna P.; Agrawal, Sonia; Sarkar, Dhiman (Scientific Reports, 2019)
Tuberculosis (TB) is the ninth leading cause of death worldwide, ranking above human immunodeficiency virus. Latency is the major obstacle in the eradication of this disease. How the physiology of the pathogen changes in transition to the latent stage needs to be understood. The latent bacteria extracted from animal hosts exist in a nonculturable (NC) phase, whereas bacteria extracted from most in vitro models are culture-positive. In the present study, we observed that nitrite, up to a concentration of 5 mM, shows the growth of Mycobacterium tuberculosis (MTB) in liquid media, but this effect starts reversing at higher concentrations. At a concentration of 10 mM, nitrite induces rapid nonculturability of MTB at the aerobic stage. This noncultivable dormancy was confirmed by analyzing the characteristics of NC bacteria. Further differential gene expression analyses clearly supported the formation of a dormancy phenotype. This study will be helpful for the use of this bacillus as a dormancy model in future studies on TB latency.

High content screening assay for identifying inhibitors against active and dormant state intracellular Mycobacterium tuberculosis - Yeware, Amar; Agrawal, Sonia; Sarkar, Dhiman (Journal of Microbiological Methods, 2019)
The antitubercular drug development pipeline could start with an in vitro investigation of several compounds to examine their effect on active and dormant state Mycobacterium tuberculosis (Mtb). However, in vitro screening of dormant state bacilli cannot provide enough information on the simultaneous effect of a compound on the host. Therefore, we developed a live cell fluorescence based screening protocol by utilizing the high content system for determining the effect of inhibitors against active and dormant state intracellular mycobacteria. THP-1 macrophages infected with an actively growing and hypoxia derived dormant Mtb culture were standardized to develop the screening protocol. The signal to noise ratio and the Z' factor of this assay were found to be 7.5-29 and 0.6-0.8, respectively, which confirm the robustness of the protocol. The protocol was then validated with standard inhibitors. This newly developed drug screening assay offers an easy, safe, image based high content screening tool to search for novel antitubercular inhibitors against both active and dormant state intracellular mycobacteria. Therefore, this assay could fill in the gap between in vitro and in vivo latent tuberculosis drug screening programs.

Using diphenyleneiodonium to induce a viable but non-culturable phenotype in Mycobacterium tuberculosis and its metabolomics analysis - Yeware, Amar; Gample, Suwarna; Agrawal, Sonia; Sarkar, Dhiman (Plos One, 2019)
Depletion of oxygen levels is a well-accepted model for induction of non-replicating, persistent states in mycobacteria. Increasing the stress levels in mycobacterium bacilli facilitates their entry into a non-cultivable, dormant state. In this study, it was shown that diphenyleneiodonium, an inhibitor of NADH oxidase, induced a viable, but non-culturable state in mycobacteria, having similar features to dormant bacilli, like loss of acid-fastness, upregulation of stress-regulated genes and decreased superoxide levels as compared to actively growing bacilli. Comprehensive, untargeted metabolic profiling also confirmed a decrease in biogenesis of amino acids, NAD, unsaturated fatty acids and nucleotides. Additionally, an increase in the level of lactate, fumarate, succinate and pentose phosphate pathways along with increased mycothiol and sulfate metabolites, similar to dormant bacilli, was observed in the granuloma. These non-cultivable bacilli were resuscitated by supplementation of fetal bovine serum, regaining their culturability in liquid as well as on agar medium. This study focused on the effect of diphenyleneiodonium treatment in causing mycobacteria to rapidly transition from an active state into a viable, but non-cultivable state, and comparing their characteristics with dormant phenotypes.

Anticancer potential of AgNPs synthesized using acinetobacter sp. and curcuma aromatica against HeLa cell lines: a comparative study - Nadhe, Shradhda B.; Tawre, Madhumita S.; Agrawal, Sonia; Chopade, Balu A.; Sarkar, Dhiman; Pardesi, Karishma (Journal of Trace Elements in Medicine and Biology, 2020)
Background: Biogenic nanoparticles are gaining attention due to their low toxicity and numerous biomedical applications. Present study aimed to compare the potential anticancer activity of two biogenic silver nanoparticles (bAgNPs and pAgNPs) against human cervical cancer cell lines (HeLa). Methods: bAgNPs were synthesized using Acinetobacter sp. whereas pAgNPs were synthesized using aqueous root extract of Curcuma aromatica. Effect of these nanoparticles on HeLa cells viability was studied using MTT assay and colony formation assay. Anticancer potential was determined using fluorescence microscopy and flow cytometry studies. Bio-compatibility studies were performed against peripheral blood mononuclear cells (PBMCs). Results: Both the nanoparticles showed 50 % viability of peripheral blood mononuclear cells (PBMCs) when used at high concentration (200 mu g/mL). IC50 for bAgNPs and pAgNPs against HeLa cells were 17.4 and 14 mu g/mL respectively. Colony formation ability of Hela cells was reduced on treatment with both nanoparticles. Acridine orange and ethidium bromide staining demonstrated that bAgNPs were cytostatic whereas pAgNPs were apoptotic. JC-1 dye staining revealed that the mitochondrial membrane potential was affected on treatment with pAgNPs while it remained unchanged on bAgNPs treatment. Flow cytometry confirmed cell cycle arrest in HeLa cells on treatment with nanoparticles further leading to apoptosis in case of pAgNPs. About 77 and 58 % HeLa cells were found in subG1 phase on treatment with bAgNPs and pAgNPs respectively. bAgNPs showed cytostatic effect on HeLa cells arresting the cell growth in subG1 phase, whereas, pAgNPs triggered death of HeLa cells through mitochondrial membrane potential impairment and apoptosis. Conclusion: Overall, bAgNPs and pAgNPs could be safe and showed potential to be used as anticancer nanoantibiotics against human cervical cancer cells.
Keywords: Acinetobacter sp.; AgNPs; Anticancer; Curcuma aromatica; HeLa cells; PBMCs

Novel gene similar to nitrite reductase (NO forming) plays potentially important role in the latency of tuberculosis - Agrawal, Sonia; Gample, Suwarna; Yeware, Amar; Sarkar, Dhiman (Scientific Reports, 2021)
The development of the latent phenotype of Mycobacterium tuberculosis (Mtb) in the human lungs is the major hurdle to eradicate Tuberculosis. We recently reported that exposure to nitrite (10 mM) for six days under in vitro aerobic conditions completely transforms the bacilli into a viable but non-cultivable phenotype. Herein, we show that nitrite (beyond 5 mM) treated Mtb produces nitric oxide (NO) within the cell in a dose-dependent manner. Our search for the conserved sequence of NO synthesizing enzyme in the bacterial system identified MRA2164 and MRA0854 genes, of which the former was found to be significantly up regulated after nitrite exposure. In addition, the purified recombinant MRA2164 protein shows significant nitrite dependent NO synthesizing activity. The knockdown of the MRA2164 gene at mRNA level expression resulted in a significantly reduced NO level compared to the wild type bacilli with a simultaneous return of its replicative capability. Therefore, this study first time reports that nitrite induces dormancy in Mtb cells through induced expression of the MRA2164 gene and productions of NO as a mechanism for maintaining non-replicative stage in Mtb. This observation could help to control the Tuberculosis disease, especially the latent phenotype of the bacilli.

DNA binding, antitubercular, antibacterial and anticancer studies of newly designed piano-stool ruthenium(ii) complexes - Navale, Govinda; Singh, Sain; Agrawal, Sonia; Ghosh, Chandrachur; Choudhury, Angshuman Roy; Roy, Partha; Sarkar, Dhiman; Ghosh, Kaushik (Dalton Transactions, 2022)
The chemotherapeutic potential of ruthenium(ii) complexes has recently attracted researchers' interest as antibacterial and anticancer agents. In this study, two novel half-sandwich imine-based Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6] (Ru-1) and [Ru(p-cymene)Cl(L-2)][PF6] (Ru-2)) were reported for their deoxyribonucleic acid (DNA) binding and antitubercular, antibacterial, and anticancer activities. The molecular structure of Ru-2 was obtained by single-crystal X-ray crystallography. DNA interaction studies were conducted by UV-Vis absorbance and fluorescence spectral titration which gave rise to DNA binding constants (K-b) of 1.32 x 10(6) and 1.82 x 10(6) for Ru-1 and Ru-2, respectively and the Stern-Volmer binding constant (K-SV) values for Ru-1 and Ru-2 were 1.7763 x 10(4) M-1 and 7.6 x 10(3) M-1, respectively. The in vitro antitubercular activity was evaluated against Mycobacterium tuberculosis H37Ra. The antibacterial potential of both the Ru-complexes was examined against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Bacillus subtilis) bacteria. The half-maximal inhibitory concentration (IC50) values for the antitubercular activity of Ru-1 and Ru-2 were 4.87 +/- 1.32 mu M and 5.78 +/- 0.54 mu M, respectively. A cytotoxic study of these complexes was performed against the human breast cancer cell line (MCF-7) and the human embryonic kidney cell line (HEK293) (normal cells). The study revealed meaningful activity of the Ru-1 complex against (cancer) MCF-7 cells, while the viability of HEK293 (normal) cells in the presence of Ru-2 was higher as compared to a reference drug 5FU. We suggest that these kinds of Ru-complexes could have potential for application in metallopharmaceuticals.

Design and synthesis of piano-stool ruthenium(II) complexes and their studies on the inhibition of amyloid ? (1-42) peptide aggregation - Singh, Sain; Navale, Govinda R.; Agrawal, Sonia; Singh, Haobam Kisan; Singla, Labhini; Sarkar, Dhiman; Sarma, Manabendra; Choudhury, Anghuman Roy; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Misfolding , protein aggregation have been linked to numerous human neurodegenerative disorders such as Alzheimer's, prion , Parkinson's diseases. Ruthenium (Ru) complexes have received considerable attention in studying protein aggregation due to their interesting photophysical and photo properties. In this study, we have synthesized the novel Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6](Ru-1), and [Ru(p-cymene)Cl(L-2)][PF6](Ru-2)) and investigated their inhibitory activity against the bovine serum albumin (BSA) aggregation and the A beta 1-42 peptides amyloid formation. Several spectroscopic methods were used to characterize these complexes, and the molecular structure of the complex was determined by X-ray crystallography. Amyloid aggregation and inhi-bition activities were examined using the Thioflavin-T (ThT) assay, and the secondary structures of the protein were analyzed by circular dichroism (CD) spectroscopy and transmission electron microscopy (TEM). The cell viability assay was carried out on the neuroblastoma cell line, revealing that the complex Ru-2 showed better protective effects against A beta 1-42 peptide toxicity on neuro-2a cells than the complex Ru-1. Molecular docking studies elucidate the binding sites and interactions between the Ru-complexes and A beta 1-42 peptides. The exper-imental studies revealed that these complexes significantly inhibited the BSA aggregation and A beta 1-42 amyloid fibril formation at 1:3 and 1:1 molar concentrations, respectively. Antioxidant assays demonstrated that these complexes act as antioxidants, protecting from amyloid-induced oxidative stress. Molecular docking studies with the monomeric A beta 1-42 (PDB: 1IYT) show hydrophobic interaction, and both complexes bind preferably in the central region of the peptide and coordinate with two binding sites of the peptide. Hence, we suggest that the Ru-based complexes could be applied as a potential agent in metallopharmaceutical research against Alzheimer's disease.
Keywords: Aggregation; Amyloid ?(1-42) peptide; DFT computation; Fibrillization; Molecular docking; Ruthenium complexes

Inhibition of amyloid β1-42 peptide aggregation by newly designed cyclometallated palladium complexes - Saini, Rahul; Navale, Govinda R.; Singh, Sain; Singh, Haobam Kisan; Chauhan, Rahul; Agrawal, Sonia; Sarkar, Dhiman; Sarma, Manabendra; Ghosh, Kaushik (International Journal of Biological Macromolecules, 2023)
Uncontrolled amyloid aggregation is a frequent cause of neurodegenerative disorders such as prions and Alzheimer's disease (AD). As a result, many drug development approaches focus on evaluating novel molecules that can alter self-recognition pathways. Herein, we designed and synthesized the cyclometallated pyrene (Pd-1 and Pd-3) and anthracene (Pd-2) based palladium complexes ([Pd((L-1)Cl] Pd-1, [Pd(L-2)Cl](Pd-2), and [Pd(L-3)Cl] (Pd-3)). This study explores the effect of these complexes on the aggregation, fibrillation, and amyloid formation of bovine serum albumin (BSA) and A beta(1-42) peptide. Several spectroscopic methods were used to characterize all the Pd-complexes, and the molecular structure of Pd -3 was determined by X-ray crystallography. The secondary structures were studied using circular dichroism (CD) and transmission electron microscopy (TEM), while am-yloid aggregation and inhibitory activities were investigated using the Thioflavin-T (ThT) fluorescence assay. Molecular docking of the Pd-complex (Pd-3) was done using fibril (PDB: 2BEG) and monomeric (PDB: 1IYT) peptides using Auto-dock Vina. As a result, the hydrogen bonding and hydrophobic interaction between the aromatic rings of the Pd-complexes and the amino acids of amyloid-beta peptides significantly reduced the pro-duction of ordered beta-sheets of amyloid fibrils and protein aggregation in the presence of Pd-2 and Pd-3 complexes.
Keywords: A beta(1-42) peptide; Aggregation and molecular docking; Palladium complex

Total synthesis, structure elucidation and expanded bioactivity of icosalide A: effect of lipophilicity and ester to amide substitution on its bioactivity - Dangi, Abha; Pande, Bharat; Agrawal, Sonia; Sarkar, Dhiman; Vamkudoth, Koteswara Rao; Marelli, Udaya Kiran (Organic & Biomolecular Chemistry, 2023)
The first total synthesis of icosalide A, an antibacterial depsipeptide that is unique in that it contains two lipophilic beta-hydroxy acids, has been achieved by following Fmoc solid-phase peptide synthesis in combination with solution-phase synthesis. The ambiguity in the absolute stereochemistry of icosalide A has been resolved by synthesizing the reported structures and other relevant diastereomers of icosalides and comparing their NMR data. NMR-based structure elucidation of icosalide A revealed a well-folded structure with cross-strand hydrogen bonds similar to the anti-parallel beta-sheet conformation in peptides and displayed a synergistic juxtaposition of the aliphatic sidechains. 12 analogues of icosalide A were synthesized by varying the constituent lipophilic beta-hydroxy acid residues, and their biological activities against Bacillus thuringiensis and Paenibacillus dendritiformis were explored. Most of these icosalide analogues showed an MIC of 12.5 & mu;g mL(-1) against both bacteria. Swarming inhibition by icosalides was least in B. thuringiensis (8.3%) compared to that in P. dendritiformis (33%). Furthermore, this is the first report of icosalides showing assured inhibitory action (MIC between 2 and 10 & mu;g mL(-1)) against the active stage of Mycobacterium tuberculosis and cancer cell lines such as HeLa and ThP1. This study could help optimize icosalides for anti-TB, antibacterial, and anti-cancer activities.